(untitled) (Research, Society and Development, 2020)
In the field of civil construction each step requires the elaboration of a specific project, whichare fundamental for the quality of service. In this sense, the present work is focused on the area of structures, since the needs of the Brazilian scenario in cost reduction, this study aims to perform a comparative analysis of a reinforced concrete structure, meeting the recommendations of ABNT NBR 6118 (2014). The building consists of four residential floors, located in the region of Teófilo Otoni, with an area of about 130 m² on each floor. Variations are made in the locations of the structural elements, verifying and analyzing the financial impacts, in order to identify the percentage of increase and its relevance in the final value. In the design the TQS software was used, for the quantification of costs it was adopted as base the data of the National Construction Costs and Indexes Research System (SINAPI) for the region of Minas Gerais. From the budget spreadsheets with the final costs, they obtained considerable differences, presenting a savings percentage of approximately 10%, between the worst case and the cheapest. Thus, it is concluded that the final price changes affect and show that there is the possibility of generating a cheaper structure, following the requirements of the standards and the safety of users.